THE UNVEILING THE ROLE OF ARTIFICIAL INTELLIGENCE ON READING PROCESSES - M Hasballah A Rahman; Hidayah Nor (PRIMACY Journal of English Education and Literacy, 2024)
In recent years, the utilization of artificial intelligence-powered tools in education has witnessed a significant surge. These tools offer invaluable assistance to teachers in classroom preparation and learners seeking to enhance their English language proficiency. With their considerable potential, AI-powered tools provide an affordable, effective, and efficient approach to teaching and learning. This research focuses on analyzing AI-powered tools that facilitate the reading process. Employing a qualitative research design with content analysis as the primary methodology and documentation as the technique, this study delves into the examination of selected AI-powered tools to aid in the reading process. The findings underscore the benefits and advantages of these tools when aligned with the various stages of the reading process. Specifically, ChatGPT emerges as beneficial for the pre-reading stage, while Quillbot and Paraphraser.io prove advantageous during reading. Post-reading activities can be facilitated by tools such as ChatGPT and Storywiz.io. In conclusion, based on the outcomes, the research recommends the utilization of the aforementioned AI-powered tools to enhance the reading process.